Collaborative Work Strategy in the Universidad Nacional de Costa Rica-UNA Educación de Calidad Project: Workshop Experiences - María Roxana Rodríguez Araya; Angélica Fontana Hernández (Revista Electrónica Educare)
This paper presents the experiences of a group of students with disabilities or educational needs in their professional development at the National University in Costa Rica. Based on the experience obtained in the Quality Education Project from Universidad Nacional (UNA) (UNA Educación de Calidad) between 2008 and 2012, the work team decided to focus on ways to support and follow up on this diversity group, particularly taking into consideration the collaborative work done by participants during the workshops for this period. To facilitate the project, the workshops were grouped into modules by topics. Results show the complexity and different shades of the collaborative actions between the groups of students in order to respond to the current educational reality.  Based on the results, the need for the project team to continue developing this constructivist methodology is clear in order to allow participants to continue offering their contributions to the rest of the university community using their own interests and skills.